(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
With greater mechanization in industry and an increasing in high velocity transport the incidence of head injury is increasing. The head injuries are most common and account for about one fourth of all deaths due to violence and responsible for 60% of fatal road accident. Head injury adds complexity to the problems because of the facts that in can not be completely evaluated until some times has elapsed after the alleged injury. The often , ill defined clinical manifestation , the issue of settlement of claims and deliberate malingering pose further difficulties to the aspects of fair decision . It was a retrospective study of 36 cases of head injury in 13 thanas of Dinajpur District during 1st January to December 2006. Among them 24 cases were due to Road Traffic accident, 6 cases were due to fire arms injury and 6 cases were due to assault. All the cases were autopsied in the mortuary of Dinajpur Medical College. The number of head injury due to Road Traffic accident were more about 17.64%, this was mostly due to accident , property dispute and dowry system. J. Dhaka National Med. Coll. Hos. 2014;20(01):35-36